2001
DOI: 10.1521/suli.31.3.333.24242
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward the Unification of Western Europe and Cross‐National Suicide Rates: Eight European Countries, 1973–1990

Abstract: Durkheim's (1897/1951) theory of political integration argues that when political crises occur, individuals band together to solve the problem at hand. As a result, this increased integration yields lower suicide rates. The purpose of this analysis is to examine a different component of the concept of political integration-that of attitudes. During the past couple of decades, individuals in eight Western European countries have been asked about their attitudes toward the unification of Western Europe. Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Social stress from migration and adverse discrimination was the only variable differentiating significantly Black from White adolescent referrals to the psychiatric service of a South London hospital, following deliberate self‐harm (DSH), particularly among males (Goddard, Subotsky, & Fombonne, 1996). Fernquist (2001) has tried to apply Durkheim's theory of political integration, analyzing attitudes of West Europeans to European unification. His data confirmed the hypotheses that higher political integration corresponds to a lower suicide rate.…”
Section: Suicide Correlates—risk Factorsmentioning
confidence: 99%
“…Social stress from migration and adverse discrimination was the only variable differentiating significantly Black from White adolescent referrals to the psychiatric service of a South London hospital, following deliberate self‐harm (DSH), particularly among males (Goddard, Subotsky, & Fombonne, 1996). Fernquist (2001) has tried to apply Durkheim's theory of political integration, analyzing attitudes of West Europeans to European unification. His data confirmed the hypotheses that higher political integration corresponds to a lower suicide rate.…”
Section: Suicide Correlates—risk Factorsmentioning
confidence: 99%
“…In general, these studies show an inverse relationship between religious integration and suicide rates; as religious integration increases, suicide rates decrease (Cutright and Fernquist, 2000;Fernquist, 2001aFernquist, , 2003aFernquist, , 2003bFernquist and Cutright, 1998). Unfortunately, the findings are not that simple: one study indicates this inverse relationship, but only for people aged fifteen to thirty-four and fifty-five to sixty-four (Fernquist, 2001a), while another study found this relationship only for males who were aged forty-five to fifty-four and sixty-five and older (Fernquist, 2003b). A third study's findings indicate that religious integration is inversely related to female suicide rates in countries that are highly religious and those that are not, while the inverse relationship for male suicide rates is found only in highly religious countries.…”
Section: Data Synthesismentioning
confidence: 96%
“…Unemployment is also identified as a risk factor for suicide (Fernquist, 2001a;Pritchard, 1990Pritchard, , 1992aPritchard, , 1995aPritchard, , 1995bRodell et al, 2003), with studies of unemployment and suicide rates indicating that fifteen to forty-four-year-olds (Pritchard, 1995a(Pritchard, , 1995b and males are more affected by rising unemployment (Pritchard, 1988(Pritchard, , 1995b. Additionally, there is a positive relationship between men's and women's suicide rates and female labour force participation (Cutright and Fernquist, 2000;Fernquist, 2003b;Fernquist and Cutright, 2000-01), occupational segregation and gender egalitarianism (Fernquist, 1999).…”
Section: Data Synthesismentioning
confidence: 99%